Efektivitas Organisasi Komisi Pemilihan Umum Kota Bukittinggi dalam Meningkatkan Partisipasi Pemilih pada Pemilu Serentak Tahun 2024 - Fauzan Harza, Muhammad (PUBLICNESS: Journal of Public Administration Studies, 2023)
The phenomenon of fluctuating community voter participation in the city of Bukittinggi serves as the foundation for this study. As of all the cities in the West Sumatra area, Bukittinggi City had the lowest turnout rate in the 2019 elections, with a participation rate of 78% of its citizens. The goal of this research was to evaluate the Bukittinggi City KPU organization's success in boosting turnout for the concurrent elections in 2024. A straightforward research design and a quasi-qualitative technique were used to conduct the study. Through observation, interviews, and documentation studies, the study data was collected. According to the study's findings, organizational efficacy in boosting voter turnout is rated as being relatively good in terms of planning, communication, knowledge management, and use of social media.